Improved Organ Utilization and Better Transplant Outcomes With In Situ Normothermic Regional Perfusion in Controlled Donation After Circulatory Death. Issue 2 (26th January 2023) - Oniscu, Gabriel C.; Mehew, Jennifer; Butler, Andrew J.; Sutherland, Andrew; Gaurav, Rohit; Hogg, Rachel; Currie, Ian; Jones, Mark; Watson, Christopher J.E.
Abstract : Background: . We evaluated whether the use of normothermic regional perfusion (NRP) was associated with increased organ recovery and improved transplant outcomes from controlled donation after circulatory death (cDCD). Methods: . This is a retrospective analysis of UK adult cDCD donors‚ where at least 1 abdominal organ was accepted for transplantation between January 1, 2011, and December 31, 2019. Results: . A mean of 3.3 organs was transplanted when NRP was used compared with 2.6 organs per donor when NRP was not used. When adjusting for organ-specific donor risk profiles, the use of NRP increased the odds of all abdominal organs being transplanted by 3-fold for liver ( P < 0.0001; 95% confidence interval [CI], 2.20-4.29), 1.5-fold for kidney ( P = 0.12; 95% CI, 0.87-2.58), and 1.6-fold for pancreas ( P = 0.0611; 95% CI, 0.98-2.64). Twelve-mo liver transplant survival was superior for recipients of a cDCD NRP graft with a 51% lower risk-adjusted hazard of transplant failure (HR = 0.494). In risk-adjusted analyses, NRP kidneys had a 35% lower chance of developing delayed graft function than non-NRP kidneys (odds ratio, 0.65; 95% CI, 0.465-0.901)‚ and the expected 12-mo estimated glomerular filtration rate was 6.3 mL/min/1.73 m 2 better if abdominal NRP was used ( P < 0.0001). Conclusions: . The use of NRP during DCD organ recovery leads to increased organ utilization and improved transplant outcomes compared with conventional organ recovery. Abstract :